Exploring the Potential of Nigerian Clay-Based Pozzolans for Enhancing Concrete Performance and Sustainability: A Study on Strength, Hydration, and Durability (Journal of Engineering, 2024)
This study investigated the potential of calcined clays from Nigerian deposits in the production of ternary blends of cement. Clay samples were obtained from three different locations namely: Ikpeshi, Okpilla and Uzebba. The raw clay samples were then calcined at 700°C and 800°C. Chemical and mineralogical compositions were determined for the raw and calcined clay samples using XRF and XRD respectively. The chemical composition confirmed these clays as potential pozzolans with SiO2, Al2O3, and Fe2O3 collectively exceeding 70%. XRD analysis identified kaolinite and quartz as major mineral phases in the raw clays, which transformed into metakaolin upon calcination. Compressive strength tests on mortar samples prepared with 50% substitution of Portland cement with the calcined clay and limestone, showed that Ikpeshi clay at 800°C had the best strength performance, with a strength activity index of 0.92 at 28 days, demonstrating superior pozzolanic potential. Strength development was more significant between 7 and 28 days, indicating the pozzolanic reaction's contribution to long-term strength. However, the initial strength at 3 days was lower than the reference cement due to a delayed pozzolanic reaction. XRD analysis of blended pastes revealed typical hydration phases like portlandite, C-S-H, Strätlingite, and ettringite, with the ternary blends showing reduced portlandite content, indicating absorption by the pozzolan's alumina phase. Durability assessments revealed that the ternary blends exhibited improved resistance to water and chloride ion ingress. These findings highlight the effectiveness of Nigerian calcined clays in producing durable and sustainable concrete, supporting their use as supplementary cementitious materials to reduce the environmental impact of concrete production.